Las endechas "A la fábula de Progne y Filomela" de Gonzalo Enríquez de Arana (Montilla, 1661-1738) - Martín Rodríguez, Antonio María (2004)
Edición y análisis de la versión burlesca de la historia mítica de Progne y Filomela compuesta por Gonzalo Enríquez de Arana (1661-1738).
Edition and analysis of the burlesque version of the myth of Procne and Philomela written by Gonzalo Enríquez de Arana (1661-1738).
Keywords: Enríquez de Arana y Puerto, Gonzalo, -- 1661-1738